A Concept for Improving Battery Energy Storage System Performance in a Redundant DC Microgrid Without SoC-Based Droop - Thales Augusto Fagundes; Lucas Jonys Ribeiro Silva; Marcio Von Rondow Campos; Marina Silva Camillo de Carvalho; Bruno Meneghel Zilli; Guilherme Henrique Favaro Fuzato; Ricardo Quadros Machado (IEEE Open Journal of the Industrial Electronics Society)
The redundancy strategy enhances the reliability of applications, such as medical centers, shipboard microgrids (MGs), and aircraft systems. This article proposes a redundancy-based dc MG integrating two modules: a cascaded bidirectional Cuk converter (CBC) and a cascaded bidirectional boost converter (CBB), each supported by battery energy storage systems (BESS), improving the reliability in case of module failure. In addition, a boost converter integrates the fuel cell (FC) through the CBC dc-link, employing a droop controller to regulate power production. In this context, the energy management system (EMS) balances the state of charge (SoC) among BESS units using a fuzzy-based method, avoiding SoC-based droop control and addressing nonlinearities in SoC equalization. The EMS also mitigates rapid transients due to load maneuvers on the dc link by using BESS units, and reduces stress on the FC membranes. Considering the CBB, the reliability of the BESS units is improved through battery-to-battery (B2B) equalization, enabled by the fuzzy-based method able to provide current references, thereby increasing power sharing accuracy. Therefore, the proposed solution performs improvement in the BESS equalization process, with redundancy ensuring stable dc-link voltage even during faults. Finally, infinity norm and Lyapunov’s indirect method confirm the MG stability, while lab-scale prototype demonstrates experimentally effectiveness.